Déclaration commune en réponse à un rapport publié par Mario Beaulieu, député / Joint Statement in Response to Report Released by Mario Beaulieu, M.P. - English Language Arts Network (ELAN); Quebec Writers' Federation (QWF); Quebec Drama Federation (QDF); Association of English-language Publishers of Quebec (AELAQ) (2023)
Keywords: Official Language Minority Community (OLMC)

Supporting the Economic Development of Québec’s English-Speaking Communities - Provincial Employment Roundtable (PERT) (2023)
The Provincial Employment Roundtable (PERT) is pleased to submit this brief and present it to the Standing Committee on Official Languages to contribute to its study of the economic development of official language minority communities (OLMCs). We believe this is an important study, which we hope will shed light on the needs of our community and lead to the development of new government actions that address the economic development challenges in Québec’s English-speaking communities, particularly in employment and employability.
Keywords: Official Language Minority Community (OLMC)

Synergistic Expertise Supporting Pedagogical Development and Innovation - Cooperberg, Andrea; Argento, Amanda; Turgeon, Chantal; Regan, Susan; Hackett, Teresa; Brown, Douglas; Prévost, Nathalie; Crossland, Constance (QUESCREN Education and Vitality Forum 2023, 2023)

Fostering Intergenerational Connections and Experiential Learning Through Community Gardening - Zbarcea, Andreea; Di Bartolo Rouillier, Jessica (QUESCREN Education and Vitality Forum 2023, 2023)

Canada, Quebec, and Intergovernmental Agreements to Support English-speaking Quebecers - Quebec Community Groups Network (QCGN) (2023)

Le Canada, le Québec et les accords intergouvernementaux à l'appui des Québécois d'expression anglaise - Quebec Community Groups Network (QCGN) (2023)

New CDA Orientation Guide - Leading English Education and Resource Network (LEARN) (2023)

August & September 2023 : Monteregie West Community Network - Montérégie West Community Network (MWCN) (2023)

June & July 2023 : Monteregie West Community Network - Montérégie West Community Network (MWCN) (2023)

Grâce à un financement de 1,1 million de dollars, 10 projets novateurs du FIC 2.0 prêtent assistance à 1 500 jeunes et aînés du Québec d’expression anglaise - Quebec Community Groups Network (QCGN) (2023)

Powered with $1.1 Million of Funding, 10 Innovative CIF 2.0 Projects Benefit 1,500 Youth and Seniors Across English-speaking Quebec - Quebec Community Groups Network (QCGN) (2023)

[CEDEC Newsletter] - Community Economic Development and Employability Corporation (CEDEC) (2023)

[CEDEC Newsletter] - Community Economic Development and Employability Corporation (CEDEC) (2023)

E-Newsletter - Seniors Action Quebec (2023)

Community Connections : Youth Perspectives on Mental Health - Youth for Youth Québec (Y4Y Québec) (2023)

CEDEC hopeful Official Languages Act Action Plan will have long-term impact and meaningful difference to ESCQ vitality - Community Economic Development and Employability Corporation (CEDEC) (2023)

La CEDEC a bon espoir que le plan d'action pour les langues officielles aura un effet à long terme et fera une importante différence sur la vitalité de la communauté d'expression anglaise du Québec - Community Economic Development and Employability Corporation (CEDEC) (2023)

E-Magazine : Better Economies for Better Lives - Community Economic Development and Employability Corporation (CEDEC) (2023)

Le magazine en ligne de la CEDEC : De meilleures économies pour de meilleures vies - Community Economic Development and Employability Corporation (CEDEC) (2023)

E-Newsletter - Seniors Action Quebec (2023)

Annual Report April 1, 2022 to March 31, 2023 - Quebec English-speaking Communities Research Network (QUESCREN) (2023)

Rapport Annuel du 1er avril 2022 au 31 mars 2023 - Quebec English-speaking Communities Research Network (QUESCREN) (2023)

E-Magazine : Better Economies for Better Lives - Community Economic Development and Employability Corporation (CEDEC) (2023)

Le magazine en ligne de la CEDEC : De meilleures économies pour de meilleures vies - Community Economic Development and Employability Corporation (CEDEC) (2023)

February & March 2023 : Monteregie West Community Network - Montérégie West Community Network (MWCN) (2023)

Community Connections : Youth Perspectives on Mental Health - Youth for Youth Québec (Y4Y Québec) (2023)

E-Magazine : A trusted leader of innovative collaboration among the public, private and civil society sectors - Community Economic Development and Employability Corporation (CEDEC) (2023)

Le magazine en ligne de la CEDEC : Chef de file reconnu de la collaboration innovatrice entre les secteurs public et privé et la société civile - Community Economic Development and Employability Corporation (CEDEC) (2023)

E-Magazine : A trusted leader of innovative collaboration among the public, private and civil society sectors - Community Economic Development and Employability Corporation (CEDEC) (2023)

Le magazine en ligne de la CEDEC : Chef de file reconnu de la collaboration innovatrice entre les secteurs public et privé et la société civile - Community Economic Development and Employability Corporation (CEDEC) (2023)

Impact Report 2022-2023 - 4Korners (2023)

Black Academic Scholarship Fund 2023 Award Luncheon - Black Academic Scholarship Fund (BASF) (2023)

Committee for Anglophone Social Action Annual Report - Committee for Anglophone Social Action (CASA) (2023)

Annual Report 2022-2023 - Community Health and Social Services Network (CHSSN) (2023)

Communauté du CHSSN NetLink - Community Health and Social Services Network (CHSSN) (2023)

Communauté du CHSSN NetLink - Community Health and Social Services Network (CHSSN) (2023)

Community Mobilization Model for Improving Health and Well-being of English-speaking Communities in Quebec - Community Health and Social Services Network (CHSSN) (2023)

Community Mobilization Model : For improving the health and well-being of English-speaking communities in Quebec - Community Health and Social Services Network (CHSSN) (2023)

Community NetLink - Community Health and Social Services Network (CHSSN) (2023)

Community NetLink - Community Health and Social Services Network (CHSSN) (2023)

Investing in the Vitality of English-speaking Quebec / Investir dans la vitalité du Québec d'expression anglaise - Community Health and Social Services Network (CHSSN) (2023)
Keywords: Official Language Minority Community (OLMC)

L’initiative sur la jeunesse et la santé mentale : Rapport d'impcat 2022-2023 - Community Health and Social Services Network (CHSSN) (2023)
Au cours de la deuxième année de l'initiative sur la jeunesse et la santé mentale (surnommée « YMHI »), le CHSSN a soutenu 27 organismes communautaires avec plus de 373 partenariats dans 12 régions du Québec, y compris trois organismes provinciaux, dans le but principal d'améliorer l'accès aux services et aux ressources en matière de santé mentale pour les jeunes d’expression anglaise du Québec âgés de 15 à 29 ans. Chaque organisation s'est efforcée d'identifier les lacunes dans les services de santé mentale pour les jeunes, d'impliquer ces derniers dans la conception des programmes, d'établir des partenariats avec les écoles locales, les services de santé publique et d'autres organisations communautaires, d'adapter, de traduire et de produire des ressources, et d'offrir des activités et des programmes pour les jeunes afin de contribuer à combler certaines lacunes. Grâce à une communauté de pratique et à un soutien individualisé, le CHSSN aide les organismes communautaires à renforcer leurs connaissances, à travailler en réseau et à résoudre les problèmes liés à la mise en oeuvre de leur programme.

Networking and Partnership Initiative / Initiative de réseautage et de partenariat (NPI) - Community Health and Social Services Network (CHSSN) (2023)

Youth Mental Health Initiative : Impact Report 2022-2023 - Community Health and Social Services Network (CHSSN) (2023)
Within the Youth Mental Health Initiative’s (YMHI) second year, CHSSN supported 27 community organizations with over 373 partnerships across 12 regions of Quebec including three provincial organizations, with the central goal of improving the access of mental health services and resources to Quebec’s English-speaking youth between the ages of 15-29. Each organization has worked to identify gaps in youth mental health services; engage youth in program design; partner with local schools, public health services and other community organizations; adapt, translate, and produce resources; and offer activities and programs for young people to help fill some of the gaps. Through a community of practice and individualized support, CHSSN helped community organizations to build their knowledge, network with each other and problem solve on program implementation.

Annual Report 2022-2023 - English Speaking Catholic Council (2023)

Learning Landscapes Journal : Education in a Pivotal Time : The Moment for Inspiration, Innovation, and Change - Leading English Education and Resource Network (LEARN) (2023)

2022-2023 Activity Report - Literacy Quebec (LQ) (2023)

Annual Report : 2022-2023 - Montérégie West Community Network (MWCN) (2023)

Annual Report : 2022-2023 - NDG Community Council (NDGCC) (2023)

Annual Report : 2022-2023 - NDG Community Council (NDGCC) (2023)

Annual Report 2021-2022 - Provincial Employment Roundtable (PERT) (2023)

Annual Report 2022-2023 - Provincial Employment Roundtable (PERT) (2023)

Strategic Plan 2024-2027 : The Way Forward - Provincial Employment Roundtable (PERT) (2023)
The Provincial Employment Roundtable (PERT) is a non-profit multi-stakeholder initiative focused on addressing the employment and employability challenges facing Québec’s English-speaking community. This strategic plan for 2024-2027 outlines five key shifts, the introduction of a third organisational pillar, and eleven strategic goals that will guide PERT’s efforts to address the unique employment challenges faced by English speakers in Québec.

Fostering Great Working Relationships in Your School Community - Quebec Federation of Home and School Associations (QFHSA) (2023)

Renforcer la vitalité des communautés d'expression anglaise du Québec : Cadre normatif 2022-2025 - Québec. Secrétariat aux relations avec les Québécois d’expression anglaise (SRQEA) (2023)

Annual Report - Réseau de l’est de l’île pour les services en anglais (REISA) (2023)

Annual Report 2022-2023 - Seniors Action Quebec (SAQ) (2023)

Rapport annuel 2022-2023 - Seniors Action Quebec (SAQ) (2023)

Townshippers' Association Annual Report 2022-2023 - Townshippers' Association (2023)

Annual Report - Vision Gaspé-Percé Now (2023)

Annual Report - Voice of English-speaking Quebec (VEQ) (2023)

The Yellow Door : 2022-2023 Annual Report / La Porte Jaune : 2022-2023 Rapport annuel - Yellow Door (2023)

Charting the Course : 2022-2023 Year in Review - Youth for Youth Québec (Y4Y Québec) (2023)

Community Connections : Youth Perspectives on Mental Health - Youth for Youth Québec (Y4Y Québec) (2023)